2014
DOI: 10.1194/jlr.p045369
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the active smoking and high-sensitivity C-reactive protein relation in late adolescence

Abstract: This article is available online at http://www.jlr.org behavioral and lifestyle factors over the life course. Infl ammation is a major component of atherosclerosis and an important factor in the early phase of arteriosclerosis ( 1 ). C-reactive protein (CRP), an acute phase reactant and a biomarker of systemic infl ammation, is associated with adverse cardiovascular outcomes ( 2 ). There is also strong evidence that CRP is an independent predictor of increased cardiovascular risk ( 3 ), supporting a role for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…In our study we showed that at age 17, males had higher intakes of dietary fibre than females, and that females had higher concentrations of hs-CRP, leptin, and adiponectin than males, consistent with previous work in this cohort at 14 (53) and 17 years (54,55) . Similar higher levels of hs-CRP in women than men were also observed in a national study of young American adults (56) .…”
Section: Https://doiorg/101017/s0007114520001609supporting
confidence: 92%
“…In our study we showed that at age 17, males had higher intakes of dietary fibre than females, and that females had higher concentrations of hs-CRP, leptin, and adiponectin than males, consistent with previous work in this cohort at 14 (53) and 17 years (54,55) . Similar higher levels of hs-CRP in women than men were also observed in a national study of young American adults (56) .…”
Section: Https://doiorg/101017/s0007114520001609supporting
confidence: 92%
“…All models found a positive association between elevated levels of CRP and Obesity and this relationship varied across gender and race. The findings in this study with regard to the association between the ln(CRP)-BMI association and estimate curves are matched with the findings of previous studies [15][16][17][18][19][20][21]. However, The FP method provided a better model fit compared to other statistical models (linear, quadratic, and categorical).…”
supporting
confidence: 78%
“…At 17 y, venous blood samples were obtained after an overnight fast for the determination of adiponectin (µg/L), leptin (µg/L) and hs-CRP (mg/L) that were measured in the PathWest Laboratory at Royal Perth Hospital (Ridker 2003, Le-Ha, Beilin et al 2012). hs-CRP was measured by an immunoturbidimetric method on the Architect c16000 Analyser (intra-assay CV 15.96%).…”
Section: Clinical and Metabolic Measuresmentioning
confidence: 99%